A systematic review of soil erosion control practices on the agricultural land in Asia - Nasir Ahmad, Nur Syabeera Begum; Mustafa, Firuza Begham; Muhammad Yusoff, Safiah @ Yusmah; Didams, Gideon (International Soil and Water Conservation Research, 2020)
Soil is the basis of production in agriculture activities. The combination of intensive farming activities, improper farming practices, rainfall regimes, and topography conditions that taken place in agricultural land lead to the soil erosion problem. Soil erosion is the major constraint to agriculture that affects the yield production and degraded environmental sustainability. Furthermore, soil erosion that occurs in the agricultural area has jeopardized the sustainability of agriculture activities. Asia is one of the major agricultural producers in the world. It is essential to know how to mitigate soil erosion in Asian agricultural land. This systematic review aims to analyze the existing literature on research that has been done on control practices that had been taken in Asia agricultural land towards soil erosion. This article is guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analysis) review method. The authors systematically reviewed the literature to study the control practices that been taken and tested to control soil erosion on the agricultural land in Asia. Accordingly, this systematic review identified 39 related studies about the topic based on the Web of Science and Scopus databases. This article divided the control practices into three main themes, which are agronomic practices, agrostological practices, and mechanical practices. The three main themes then produced a total of 11 sub-themes. Further specific and sustained research is needed to tackle this severe environmental problem through a better method, such as this systematic review method. The systematic review helps farmers and policymakers to implement the most practical approach to control and reduce soil erosion.